Implementasi Peraturan Daerah Kota Sukabumi Nomor 10 Tahun 2013 Terhadap Kegiatan Gebyar Kuliner di Kawasan Eks Terminal Sudirman Kota Sukabumi - Bunga Ananda Desdhenyra; Agus Rasyid Chandra Wijaya (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the implementation of Sukabumi City Regulation No. 10 of 2013 regarding the Gebyar Kuliner event in the former Sudirman Terminal area of Sukabumi City. This study was motivated by the increasing activity of street vendors who utilize public spaces as centers of community economic activity. However, in practice, various problems related to order, cleanliness, and the use of public facilities are still frequently encountered. The research method used by the author is a juridical-empirical approach with a descriptive-analytical approach. Data was collected through field observations and interviews with local government officials, vendors, and the surrounding community. The research results indicate that the implementation of this local regulation has not yet been optimal; this is due to a lack of oversight by the Sukabumi city government, as well as low legal awareness among street vendors. Nevertheless, the existence of the Gebyar Kuliner event has had a positive impact on improving the local economy and developing the micro, small, and medium enterprise (MSME) sector in Sukabumi City. This study concludes that the implementation of Sukabumi City Regional Regulation No. 10 of 2013 still requires strengthening in terms of oversight, legal awareness campaigns, and the provision of adequate facilities to achieve a balance between public order and the economic empowerment of the community.